(untitled) (World Science, 2021)
The unique properties of epoxy polymers have led to their wide application in various fields of modern technology. The influence of the structure of bisphenols on the properties of epoxy polymers, especially thermal ones, is known. However, the chemical structure of the hardener also affects the properties of cured epoxy polymers. As hardeners, we used acid hardeners of various structures: anhydrides of maleic, phthalic, pyromellite, methyltetrahydrophthalic and other acids. The following hardeners give high results in heat resistance: pyromellite and methyltetrahydrophthalic anhydrides. Polymers obtained by curing with these hardeners are deformed in the temperature range of 220-245°C. The use of these hardeners gives high results in terms of thermal stability. These polymers are formed by curing these components. It is known that the properties of epoxy polymers depend on the chemical structure of the glycide ether. There was some interest in investigating the influence on the properties of epoxy polymers as a chemical structure, as well as the nature of hardeners. For this purpose, diglycidal esters based on bisphenols were synthesized.